A Brief Review on Extraction and Use of Pectin from Natural Sources - Uysal, Selma Yarligan; Maihan, Robina (Challenges and Advances in Chemical Science Vol. 5, 2021)
Pectin of various strengths to gel or stabilize stocks, as well as pectin of various standards or derivatives with simple properties, is in high demand. While pectin is commonly used as a food ingredient in jellies, syrups, and dairy products for its densification, gelling, and emulsifying capabilities, it is also classified as a biodegradable polymer with natural sources, but its supply is limited. To get a significant yield of high-quality pectin, some factors, such as the extraction process requirements, must increase the stability of the reaction by releasing high solvent polymers with negative charges and hydrolyzing the glycoside or ester bond. Therefore, time, temperature, and HNO3 concentration are the autonomous factors. In this review, it is intended to provide a comprehensive overview of the current state of pectin research by focusing on recent studies of pectin recovery from plant materials (purification and fractionation) as well as advances in the physical, chemical, and functional properties of pectin.